Judicial Pardon Implementation under The 2023 Indonesian Criminal Code: Regulatory Analysis and Juridical Implications - Feby Reski Utami; Litya Surisdani Anggraeniko; M. Reyhan Aldabena (Universitas Negeri Semarang, 2026)
The enactment of the new Criminal Code (Law Number 1 of 2023) introduces a significant reform to Indonesia's sentencing system by explicitly regulating of Judicial Pardon. This concept empowers judges to refrain from imposing a criminal penalty or measure on a defendant proven guilty of a criminal act, based on considerations of justice and humanity. This study aims to conduct a constructive legal analysis of Judicial Pardon within the new Criminal Code, examining the limits of judicial discretion in its application and the legal implications for harmonizing legal certainty with substantive justice. The study employs a normative legal research methodology, utilizing statutory, conceptual, and literature review approaches. The findings indicate that the explicit inclusion of Judicial Pardon in the new Criminal Code represents a paradigm shift from formal legalism toward substantive justice, achieved through the application of principles such as the individualization of sentencing and restorative justice. However, the lack of clear normative parameters in Article 54 paragraph (2) of the Code creates a potential risk of sentencing disparities, the abuse of judicial discretion, and compromised legal certainty. Therefore, clear boundaries are required, grounded in the principles of proportionality and propriety, as well as the harmonization of the Criminal Code with the Criminal Procedure Code and the Law on Judicial Power to ensure that Judicial Pardon functions as an instrument of substantive justice without undermining legal certainty or judicial accountability.